Intensitas dan Insidensi Serangan Penyakit Layu Bakteri (Ralstonia solanacearum) pada Eukaliptus di Kabupaten Ogan Komering Ilir Sumatera Selatan - Djulian, Dhanillo; Muslim, Ahmad; Pratama, Rahmat; Al Gibran, Ahmad Naufal; Yudistira, M Alvin; Yonitha, Hafizhah Ega; Pangestu, Riska Mutia; Putri, Rahma (Seminar Nasional Lahan Suboptimal, 2024)
Djulian D., Muslim A., Pratama, R., Gibran, A. N. A., Yudistira, M. A., Yonitha, H. E., Pangestu, R. M., Putri, R. (2024). Intensity and incidence of bacterial wilt disease (Ralstonia solanacearum) on eucalyptus in Ogan Komering Ilir District, South Sumatera. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-12 Tahun 2024, Palembang 21 Oktober 2024. (pp. 446–460). Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Ralstonia solanacearum is a disease that attacks eucalyptus plants which is usually characterized by symptoms of wilting in the tops of leaves and young twigs which will then cause tissue death in plants. Therefore, the purpose of this study was to determine the intensity and incidence of bacterial wilt disease in PT Bumi Andalas Permai Ogan Komering Ilir. With the method of observing directly by surveying eucalyptus at PT Bumi Andalas Permai in Ogan Komering Ilir Regency, South Sumatra. The survey was conducted by taking samples of plants affected by disease in the field. Sampling method with Transect method. Samples were taken as many as 30 samples measuring 5x5 mm, ooze that was in the sample was taken and then isolated with NA media. Based on research on eucalyptus plants at PT Bumi Andalas Permai, it was found that plants of the EP4136AA clone type in the Air Sugihan district with a plant age of 10 months and a plant spacing of 1.87m per plant and in the Jeletung district with the same clone and a plant age of 11 months and a plant spacing of 1.87m had susceptibility to Ralstonia solanacearum bacterial wilt disease attack. In contrast, clones EP6098, EP0077, and EP0361 in PT Bumi Andalas Permai in Ogan Komering Ilir District are resistant to Ralstonia solanacearum disease. Attacks in both districts show different levels of intensity and incidence, in the Air Sugihan district the intensity is up to (6.063%) and the incidence is up to (16.50%) and the intensity in the Jelutung district is up to (16.688%) and the incidence is up to (17.25%). So the conclusion of this study found that eucalyptus plants attacked by bacterial wilt disease at PT Bumi Andalas Permai have intensity and incidence that fall into the heavy or high category.